Optimisation of a salt deposition technique for the corrosion-fatigue testing of nickel based superalloys - Hollie Cockings (Materials at High Temperatures, 2018)
Prior to the method developed in this paper, salting techniques for corrosion-fatigue testing in the literature were trialled and yielded anomalous laboratory-based test results and did not represent in-service gas turbine conditions. This new method has enabled test reproducibility, closely simulating in-service damage and is used within Rolls-Royce, Amec- Foster-Wheeler, Cranfield University and Swansea University as a test standard and is an underpinning technology on EP/H500383/1, EP/H022309/1, IUK113018, EP/M005607/1 (and others) enabling a full materials database to be established under high temperature corrosion-fatigue conditions. Two further EngD’s have been funded under EP/H022309/1 and EP/L015099/1, specifically to develop this work further.